Design and Evaluation of an Easy-to-Use Web Playground - Guimarães, Rodrigo Laiola; Motta, Mateus Molinaro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2014: Anais Estendidos do XX Simpósio Brasileiro de Sistemas Multimídia e Web, 2014)
Learning about Web Design can be difficult and time consuming, yet students often do not learn from their errors and struggle to understand some differences between document structure, styling, scripting and temporal synchronization. In this paper we present Ambulant Sketchbook, an easy-to-use Web playground designed to enable students to understand and learn from their errors. In particular, this application simplifies the process of learning how to write and debug Web documents by exploring aspects of immediate feedback, coding assistance, direct manipulation and playback control. We have deployed and used Ambulant Sketchbook in a course of Web Design Foundations over a 2- week span. Based on the positive feedback from a group of postsecondary students, we expect the functionalities and experiences discussed in this work can yield significant insights to be considered in the design of next generation authoring tools and in the process of teaching Web Media related disciplines.